How to develop ethnoscience learning as a contextual learning strategy in madura primary school - Andika Adinanda Siswoyo (Universitas Muhammadiyah Surabaya, 2020)
Abstract. This study aims to know how the implementation of etnoscience learning in primary schools. This research is a qualitative descriptive type. This research was conducted in Madura Primary School. The research instrument used was an observation sheet, and documentation. Based on research result, Ethnoscience learning strategies can be done interactively with subjects, taught on individual subjects, and taught separately. As for the strategy of learning in implementing Ethnoscience-based learning in order to realize the character of elementary school students by Choosing the models used are: a.) Complementary modeling (single subject) implantation